2006
DOI: 10.1097/01.cpm.0000203745.50250.3b
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Cord Dysfunction

Abstract: Vocal cord dysfunction, a syndrome of paradoxical inspiratory closure of the vocal cords, is becoming more frequently recognized and diagnosed recently since its initial modern description 30 years ago. Initially described as single case reports, the first case series in 1983 helped to clarify the typical patient and findings of vocal cord dysfunction. Recent investigations have elucidated specific etiologies such as gastroesophageal reflux, exercise, and irritants as causative factors in addition to the numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(27 citation statements)
references
References 161 publications
(216 reference statements)
1
19
0
7
Order By: Relevance
“…In addition, there tends to be a female predominance among patients with VCD. Brugman and colleagues found a 3:1 female predominance among their patients, while Morris and colleagues studied 1161 patients in another literature review and found a 2:1 female predominance [8]. …”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, there tends to be a female predominance among patients with VCD. Brugman and colleagues found a 3:1 female predominance among their patients, while Morris and colleagues studied 1161 patients in another literature review and found a 2:1 female predominance [8]. …”
Section: Clinical Presentationmentioning
confidence: 99%
“…It is still thought that psychological stimuli can trigger VCD, including anxiety disorder, stress, depression, somatoform disorder, conversion disorder, psychiatric illness, history of sexual abuse, and mass psychogenic illness [18]. In a case series published in 1983 of five patients with “uncontrolled” asthma and dramatic wheezing all found to have VCD, a psychiatrist performed personality testing prior to any physiologic or laryngoscopic studies and established a psychiatric diagnosis in four of the five patients [8]. In a review by Lacy and McManis in the late 1990s, 45 of 48 patients had a psychiatric condition, including conversion disorder (52 %), major depression (13 %), factitious disorder (10 %), obsessive-compulsive disorder (4 %) or adjustment disorder (4 %) [30].…”
Section: Disease Mechanism and Triggersmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact incidence or prevalence of this condition is not clearly known, as there are no large-scale studies for this disorder. Most case series have noted a greater prevalence in females (5, 6) and 29% cases occurring in those <18 years of age (7), with an average age of 14.5 years in adolescents and 33 years in adults (2). Nevertheless, prompt recognition and treatment is crucial, as inappropriate treatment has been associated with significant costs and morbidity.…”
Section: Introductionmentioning
confidence: 99%